(untitled) (المجلة الدولية للبحوث العلمية, 2024)
This study contains a comparison between the two Kalman filter and adaptive filter has huge importance because of it is uses in different applications such as air navigation planes, satellites, cameras, motions, radar, stations. Adaptive filter has various Application as well and important in CCTV and microphones.